Analysis of chicken transcriptomes to predict functions of novel genes - Ravi, Sharanya; Mat Isa, Nurulfiza; Omar, Abdul Rahman; Bejo, Mohd Hair; Ideris, Aini (Faculty of Veterinary Medicine, Universiti Putra Malaysia, 2015)
IBDV infection has long been studied to have adverse effects of poultry industry. Discovery of vaccines against the disease has still not proven to completely control the same. With that as the primary goal this study aims to look at novel genes that could be potential targets against the disease or could give more information about the pathogenicity of the virus. In this study Transcriptomes from RNA-seq analysis was obtained for 6 different cell lines infected with IBDV. The set of sequences that did not map to the reference genome of Gallus gallus were analysed to search for novel gene that is differentially expressed due to IBDV infection. To understand the function of unknown sequences networks were generated using the R tool WGCNA (Weighted Gene Correlation Network Analysis) which primarily looks at the most correlated genes and clusters them into modules. Thus it becomes easy to identify the functions of those sequences that have not been annotated before. Out of ~10,800 sequences that did not map with the reference genome, most significant sequences (log2 fold change <-2 or >2) were filtered (~600). The predicted functions of the commonly up regulated and down-regulated sequences (12 up-regulated and 18 down-regulated) were found to be immune related and extracellular binding related respectively. These predictions enable us to further confirm the presence of these sequences in the chicken tissue and help focus on them as potential drug targets. Further work on these sequences would include analysis of the structure of the protein they translate and examine to see if they could be a drug target.